Phytochemical Content, Inorganic Composition, Mineral Profile, and Evaluation of Antioxidant Activity of Some Common Medicinal Plants - Al-Salman, Fadheela; Redha, Ali Ali; Aqeel , Zainab; Ali, Zahra (Iraqi Journal of Science, 2022)
The current research focuses on the antioxidant activity, phytochemical, and inorganic content of five common medicinal plants: Asian pigeonwings, lemon balm, lemongrass, ginger, and turmeric. According to the phytochemical screening, flavonoids were present in all plants; tannins were present in lemon balm and lemongrass, saponins were present in all plants except lemongrass, and anthraquinone glycosides were detected only in turmeric. The aqueous extracts from lemon balm, Asian pigeonwings, and the methanolic extract from turmeric had the highest phenolic content, respectively. The inorganic composition of plants was determined using energy dispersive X-ray fluorescence. Asian pigeonwings, ginger and turmeric are mainly composed of K, while lemon balm and lemongrass are mainly composed of Ca. The mineral profile of each herb was determined by inductively coupled plasma-optical emission spectrometry analysis. The antioxidant activity of each herb was determined by the 2,2-diphenyl-1-picrylhydrazyl radical scavenging activity assay. Among the extracts, the aqueous extract from ginger had the highest antioxidant activity with a percentage of 88.05 ±0.31 %.